Acquired coronary artery disease in adult patients with congenital heart disease: a true or a false problem?. Issue 8 (August 2017) - Giamberti, Alessandro; Lo Rito, Mauro; Conforti, Erika; Varrica, Alessandro; Carminati, Mario; Frigiola, Alessandro; Menicanti, Lorenzo; Chessa, Massimo
Abstract : Background: The population of adults with congenital heart disease (ACHD) is increasing and aging, and a large percentage of this population is now over 65 years of age. For this reason, it is probable that acquired coronary artery disease (CAD) will become an important issue that needs to be addressed also in these patients. We retrospectively analyzed all ACHD patients who underwent surgery in our Institution with the aim to investigate the incidence of associated CAD and the results of surgical treatment. Methods: From January 2000 to December 2015, a total of 1154 ACHD underwent surgery in our center. Fifty patients (4.3%) were diagnosed with acquired CAD and required coronary artery bypass grafting. The mean age at surgery was 66 years (range 41–78 years). The primary diagnosis were atrial septal defect ( n = 40 patients), Tetralogy of Fallot ( n = 4 patients), ventricular septal defect ( n = 2 patients), partial AV canal ( n = 1), partial anomalous pulmonary venous drainage ( n = 1), Ebstein's anomaly ( n = 1), and subaortic stenosis ( n = 1). Results: Hospital mortality was 2% (one patient). During a mean follow-up of 9 years (maximum follow-up: 15 years), seven patients died (14%). The actuarial survival was 83% at 5 years and 77% at 10 years. Freedom from reoperation for coronary artery bypass grafting or percutaneous coronary intervention was 88% at 5 years and 82% at 10 years. Conclusion: Acquired CAD may coexist with congenital heart defects but the association is quite rare. It typically occurs later during adulthood and it is usually associated with atrial septal defect. Acquired CAD and congenital heart defects can be treated contemporarily with good early and late results.